(1) A=[-1,3]
所以
m-2=1且m+2≥3
得m=3,m≥1 符合题意
所以m=3
(2)CRB={x/xm+2}
所以3=m+2
即m>=5或mx - 2x - 3 ≤ 0
(x + 1)(x - 3)≤ 0
-1 ≤ x ≤ 3
所以
A = {x| -1 ≤ x ≤ 3}
B = {x|m - 2 ≤ x ≤ m + 2 }
(1)
A∩B = [0,3]
则 m - 2 = 0 , m + 2 ≥ 3
所以 m = 2
(2) CrB = {x | x < m - 2 或 x > m + 2 }
因为 A∩CrB = A
所以 m + 2 < 0 或 m - 2 > 3
所以 m < -2 或 m > 5x - 2x - 3 ≤ 0
(x + 1)(x - 3)≤ 0
-1 ≤ x ≤ 3
所以
A = {x| -1 ≤ x ≤ 3}
B = {x|m - 2 ≤ x ≤ m + 2 }
(1)
A∩B = [0,3]
则 m - 2 = 0 , m + 2 ≥ 3
所以 m = 2
(2) CrB = {x | x < m - 2 或 x > m + 2 }
因为 A∩CrB = A
所以 m + 2 < 0 或 m - 2 > 3
所以 m < -2 或 m > 5下面发给你的是更加详细的解答,希望能帮到你